Hypercalcemia as a rare presentation of angioimmunoblastic T cell lymphoma: a case report - Sana Chams; Inaya Hajj Hussein; Skye El Sayegh; Nour Chams; Khalid Zakaria (Journal of Medical Case Reports, 2018)
Abstract Background Angioimmunoblastic T cell lymphoma is a rare malignancy, accounting for only 2% of all non-Hodgkin lymphomas, first described in the 1970s and subsequently accepted as a distinct entity in the current World Health Organization classification. Due to the paucity of this disease, there is still no identifiable etiology, no consistent risk factors, and the pathogenesis remains unclear. Case presentation An 83-year-old Caucasian man presented to an emergency department with palpitations and was found to have atrial fibrillation. During his hospitalization, he was found to have asymptomatic hypercalcemia with corrected calcium of 11.7. Ten days later while in rehabilitation, he started complaining of progressive fatigue and altered mental status was noted. He was found to have a calcium level of 15.5 and was admitted to the intensive care unit for management and further workup. He was found at that time to have, parathyroid hormone: < 1; 25 hydroxyvitamin D: 74; 1,25 dihydroxyvitamin D: 85.4; angiotensin-converting enzyme: 7; parathyroid hormone-related protein: < 2; and multiple myeloma workup was negative. Computed tomography of his chest and abdomen showed extensive retroperitoneal, pelvic, and mesenteric lymphadenopathy in addition to findings suggestive of peritoneal carcinomatosis. A right axillary lymph node biopsy showed immunohistochemical parameters consistent with angioimmunoblastic T cell lymphoma. After a lengthy discussion with his family, it was decided that no further treatment would be pursued. He had an aggressive course at the hospital during which he developed pleural effusions, ascites, and diffuse petechiae within 2 weeks; these were complications from his malignancy. Considering the poor outcomes of his aggressive disease, he decided to enroll in an out-patient hospice. He died within a few months as a result of cardiorespiratory arrest. Conclusions This case illustrates a rare presentation of an extremely rare disease; that is, hypercalcemia in a patient who was later found to have angioimmunoblastic T cell lymphoma. Diagnosing angioimmunoblastic T cell lymphoma might be the most challenging part due to the wide array of clinical presentations, of which hypercalcemia accounts for only 1%. As seen in this case, most patients present in advanced stages of the disease with poor prognosis.